2021
DOI: 10.1038/s41598-021-87411-8
|View full text |Cite
|
Sign up to set email alerts
|

A graph neural network framework for causal inference in brain networks

Abstract: A central question in neuroscience is how self-organizing dynamic interactions in the brain emerge on their relatively static structural backbone. Due to the complexity of spatial and temporal dependencies between different brain areas, fully comprehending the interplay between structure and function is still challenging and an area of intense research. In this paper we present a graph neural network (GNN) framework, to describe functional interactions based on the structural anatomical layout. A GNN allows us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 106 publications
2
21
0
Order By: Relevance
“…In this spirit, propagating the information between ROIs based on their SC or structural CE similarity can give us a multimodal perspective of such a directed relationship between brain areas. In the following we choose a perturbation base approach to reconstruct the amount of information one ROI carries about other ROIs [85,79]. By learning a function h(•), the GNN models try to infer from an input sequence of neural activity states [x (1) , .…”
Section: Multimodal Directed Connectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…In this spirit, propagating the information between ROIs based on their SC or structural CE similarity can give us a multimodal perspective of such a directed relationship between brain areas. In the following we choose a perturbation base approach to reconstruct the amount of information one ROI carries about other ROIs [85,79]. By learning a function h(•), the GNN models try to infer from an input sequence of neural activity states [x (1) , .…”
Section: Multimodal Directed Connectivitymentioning
confidence: 99%
“…Different brain areas communicate via bioelectrical signals transmitted along neuronal axons and collected by neuronal dendrites. Spatio-temporal GNNs provide a novel possibility to incorporate such a structural scaffold into a graph-based prediction model [79]. Due to cognitive information processing in the brain, the spatial interactions of the activity distribution changes dynamically.…”
Section: Graph Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the flatness of Euclidean spaces means that certain operations require many dimensions and complex computations to perform, whereas non-Euclidean spaces may perform these operations more flexibly with fewer dimensions. The graph structure breaks the uniform distribution of the commonly used Euclidean grid structure and can better represent the structural connections and functional realization of brains (Wein et al, 2021 ). It has been used in the diagnosis of autism spectrum disorders (Yang et al, 2021a ), fMRI analysis (Li et al, 2019b , 2021b ), brain network analysis (Wu et al, 2021 ; Royer et al, 2022 ), brain-computer interface decoding (Feng et al, 2021 ; Che et al, 2022 ), emotion classification (Liu et al, 2022 ), and epilepsy detection (Zhao et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Learning the representation of the brain connectome has both positive and negative potential social implications, as it can be linked to the search for new biomarkers of a particular phenotype. Accordingly, the current trend in studies attempting to apply GNN to the brain connectome is to input the FC graph from either resting-state [19,20,2,24,18,35,36] or task fMRI data [21][22][23] and predict a particular phenotype of the subjects, such as gender [20,2,18,17] or presence of a specific disease [20,24,[21][22][23]17]. While these studies have shown potential strengths and opportunities for learning the network representation of the brain, they also suggest limitations of current GNN-based methods.…”
Section: Introductionmentioning
confidence: 99%